Answer:
66
Step-by-step explanation:
12(8)-9(8-6)-(12-9)(8)÷2=96-18-12 or 6(9)+(12-9)(8)/2=54+12
= 66 =66
Answer: hope this will help you
Step-by-step explanation:
Plz mark me as brainlist
Answer:
21
Step-by-step explanation:
I set it up as a table and found the equation. With increasing student counting it increases by six. So 6 times the number of students of counting gives you your output (y).
Input | Output Equation: 6x = y
1 6
2 12
3 18
4 24
5 30
.... .....
19 114
20 120
21 126
Hope this makes sense